2013
DOI: 10.1186/scrt160
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal interactions of mouse bone marrow-derived mesenchymal stem cells and BV2 microglia after lipopolysaccharide stimulation

Abstract: IntroductionMesenchymal stem cells (MSCs) are immunosuppressive, but we lack an understanding of how these adult stem cells are in turn affected by immune cells and the surrounding tissue environment. As MSCs have stromal functions and exhibit great plasticity, the influence of an inflamed microenvironment on their responses is important to determine. MSCs downregulate microglial inflammatory responses, and here we describe the mutual effects of coculturing mouse bone marrow MSCs with BV2 microglia in a lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 54 publications
4
44
1
Order By: Relevance
“…inflammatory (M1-like) into an anti-inflammatory (M2-like) phenotype [26,31,36] mainly through COX-2 mediated production of PGE2 and possibly some other soluble factors [35,37]. Similar PGE2-mediated interaction was also described between other tissue macrophages and MSCs in vitro [12], as well as in vivo [43].…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 77%
See 1 more Smart Citation
“…inflammatory (M1-like) into an anti-inflammatory (M2-like) phenotype [26,31,36] mainly through COX-2 mediated production of PGE2 and possibly some other soluble factors [35,37]. Similar PGE2-mediated interaction was also described between other tissue macrophages and MSCs in vitro [12], as well as in vivo [43].…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 77%
“…However, the precise polarization states of microglia in the presence of MSCs under physiological or inflammatory conditions remain largely unknown. In most studies, xenogenic experimental systems were used; that is, cocultures of human MSCs with mouse or rat MGs [26,[31][32][33] and primary microglia were frequently replaced with neoplastic cell lines (BV2 or N9) [34][35][36] or with hippocampal slices [37]. Only two laboratories used autologous mouse [35] or rat [38] primary MGs and MSCs.…”
Section: Au3 Cmentioning
confidence: 99%
“…These findings are still to be elucidated, as a variety of regulatory mechanisms are involved in controlling iNOS expression [41]. The increase in NO production has also been shown in coculture systems of MSC with T cells [42,43] and microglia [17,18]. In general, the excessive amount of NO can cause neurotoxicity [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…There were also numerous studies using MSC as a therapeutic tool in various models of neuroinflammation [27,28,29]; MSC demonstrate immunomodulatory effects on microglia [15,16,17,18]. In addition, several studies have shown that MSC-CM accelerates wound healing [30,31], promotes liver regeneration [32] and improves cardiac function following myocardial infarction [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation